Отбор информативных признаков на основе квантовых вычислений - Комендант, А. В.; Субботин, С. А. (Видавництво Львівської політехніки, 2011)
The method of feature selection based on quantum computing is offered. It can improve the quality and speed of diagnostic model synthesis.
Keywords: feature selection; quantum computing; technical diagnosis